Battling terrorism in the Horn of Africa - Rotberg, Robert I. (World Peace Foundation ; Brookings Institution Press, 2005)
"Examines the state of governance in the countries of the greater Horn of Africa region--Djibouti, Eritrea, Ethiopia, Kenya, Somalia, the Sudan, and Yemen--and discusses strategies to combat the transnational threat of terrorism, including suggestions for more effective U.S. engagement in the region"--Provided by publisher.